Pride Parades and LGBT Movements - Peterson, Abby (Gender and Comparative Politics, 2018)
The Open Access version of this book, available at http://www.tandfebooks.com/doi/view/10.4324/9781315474052, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license Today, Pride parades are staged in countries and localities across the globe, providing the most visible manifestations of lesbian, gay, bisexual, trans, queer and intersex movements and politics. Pride Parades and LGBT Movements contributes to a better understanding of LGBT protest dynamics through a comparative study of eleven Pride parades in seven European countries　- Czech Republic, Italy, Netherlands, Poland, Sweden, Switzerland, the UK　- and Mexico. Peterson, Wahlström and Wennerhag uncover the dynamics producing similarities and differences between Pride parades, using unique data from surveys of Pride participants and qualitative interviews with parade organizers and key LGBT activists. In addition to outlining the histories of Pride in the respective countries, the authors explore how the different political and cultural contexts influence: Who participates, in terms of socio-demographic characteristics and political orientations; what Pride parades mean for their participants; how participants were mobilized; how Pride organizers relate to allies and what strategies they employ for their performances of Pride. This book will be of interest to political scientists and sociologists with an interest in LGBT studies, social movements, comparative politics and political behavior and participation.